An effective cloud based personal emergency response system by providing privacy protection for the medical data - Brindha Devi, V; U, Lokeswari; B, Saraswathi; T, Vindhya (International Journal of Engineering and Technology, 2018)
Timely access to the emergency medical services is challenging tasks due to the increasing percentage of population. Especially prehospital emergency situations are neglected for quite a long time. The agglomeration of medical gadgets and other system applications that bridges the gap to healthcare IT systems through Internet or computer networks is placed under the domain (IoMT) Internet Of Medical Things . In this project an efficient medical data monitoring and an emergency response system has been developed. IoT in healthcare is made to bridge the gap by providing the connectivity through internet making sure that the information is secured and available on the timely access. The wireless monitoring device collects data from various sensors, which is shared into the database using ZigBee cc2530 Transmitter Receiver through UART communication. The wireless device is embedded with sensors like Pulse oximeter (senses the heart beat rate and blood oxygen concentration)and temperature sensor. This data is monitored regularly and if there is any abnormality in the values then an alert is sent to the doctor to intimate the condition of the patient. This paper provides an interaction of the patient with the doctors. The interaction is enabled using public and private chat application where any number of patients can interact with a doctor. It is challenging task to personalize specific healthcare data i.e. medical records for various application users in an appropriate and secured fashion. Thus, the patientâ€™s health records i.e. prescription, scan reports, etc. are uploaded by the patient which can be viewed by the doctor. These files are encrypted using an encryption algorithm before uploading it into the cloud. Similarly it is decrypted while downloaded by the doctor for reference. The data collected is used for the prediction of diseases like heart attack and the report is sent to the doctor. Hence the projectâ€™s aim is, when the recorded value exceeds the threshold range, an automatic intimation with the patientâ€™s collected data is sent to the concerned doctor.Â Â